Penerapan Pembelajaran Tatap Muka (PTM) Terbatas pada Mata Pelajaran Pendidikan Jasmani Selama Pandemi Covid-19 di Pesantren Mts Manbaul Hikmah Gedongan Cirebon - Muhammad Zakaria; Endang Sri Budi Herawati; Dewi Wahyuni (Indonesian Journal of Physical Education and Sport Science, 2023)
Study purpose. This study aims to describe the implementation of Limited PTM in PJOK subjects at MTs Manbaul Hikmah Pesantren Gedongan Cirebon, focusing on the implementation of learning, methods, media used, student participation, and obstacles faced by teachers and students during the PTM process. Materials and methods. The research uses a qualitative descriptive method with data collection techniques through structured interviews, direct observation, and collection of supporting documents. The research participants consisted of six informants, namely the Head of the Madrasah, the Deputy Head of the Madrasah for Curriculum, the PJOK Teacher, and three students. Data analysis is carried out thematically through the stages of transcription, coding, categorization, thematization, and triangulation of data sources to ensure the validity of the results. Results. The results of the study showed that the implementation of Limited PTM in PJOK subjects went quite well despite facing limited learning time. Teachers use assignment and discovery learning methods with the main media in the form of package books and worksheets, as well as assignments to make videos of simple sports practices. Student participation in learning activities is relatively high, although there are obstacles in terms of limited time, learning facilities, and increased workload during Limited PTM. Conclusion. Overall, the implementation of PJOK learning during the Limited PTM period can be categorized as effective with adaptive adjustments to pandemic policies and situations, and still be able to achieve basic learning goals through a simple but functional approach.